Influence of High Mud Volume On Vacuum Filter Performance A case Study- Elguneid Sugar Factory, Sudan - elsdeeg, yousra alamin; B. Mohammed, Salma; S. Hassn, kamal; Elkhalifa, Elamin A. (Gezira Journal of Engineering and Applied Sciences, 2018)
Elguneid Sugar Factory is designed for manual harvesting cane but the field labor has become scarce and wages for field work is very high. For this reason, Elguneid Sugar Factory has introduced mechanical harvesting; therefore there was an increase in the ratio of mud which enters to Elguneid Sugar Factory. This study aimed to know the influence of high mud level which resulted from mechanical harvesting on the efficiency of Rotary Vacuum Filters. The experimental tests were carried out on the Rotary Vacuum Filters of Elguneid Sugar Factory. The filter dimensions were calculated and found to be 6096 mm length, 3658mm Radius and 174m2 total filtering surface areas. The Rotary Vacuum Filters were tested under different speeds varied from 7.5-12cycle/hr.The low vacuum was 361.2mm Hg, and 412.8mm Hg for high vacuum. Washing water temperature was found to be 81oC and quantity of bagacillo for each crushed tone of cane was found 13Kg/hr. The thickness of filter cake ranged between 3.5-5.2mm which decreased with the Rotary Vacuum Filter Speed (RVFS). In this research work it was found that sucrose in filter cake ranged between 1.39-2.21%, which increased with RVFS. Also it was found, that moisture content of filter cake ranged between 60.8-62%. The increase in moisture was dependent on RVFS increase. The mud quantity was calculated and found to be 133.63-147.87Kg/hr.The filter retention was calculated and found to be 7.2% and this considered very low when compared to the international standard which was 70% as average. All these results showed that the rotary vacuum filters in Elguneid Sugar Factory has a bad performance for removal of the increasing mud level.